ABU RAYKHAN BERUNI - ENCYCLOPEDIA SCIENTIST - Oktamov Tohirjon Gayrat oglu (Web of Journals Publishing, 2025)
This article provides information about the life and scientific work of Abu Rayhan Beruni, one of the great encyclopedists of his time. Information is provided about the creation of Abu Rayhan Beruni's works and their study.
Keywords: Ubaydullo Karimov, Abu Rayhan Beruni, Kat, Ibn Iraq, Ptolemy, Jurjan, Qabus ibn Washmgir, Sahib ibn Abbad, Ghazna, Mas'ud Ghaznavi